2021
DOI: 10.11648/j.ajpb.20210604.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage Practices and Cropping Pattern on Soil Properties and Crop Yield in the Humid Lowlands of Beles Sub-Basin, Ethiopia

Abstract: Tillage is a land management practice where a sequence of manipulating the soil for crop production. To investigate the response of land management and cropping pattern on soil properties and crop yield, a field experiment was conducted under natural environment on Nitisol of Pawi area. Nine treatments combining two tillage methods (Zero and conventional), four crop covers (continuous maize, continuous soya bean, rotated maize, and maize soya bean intercrop) were laid out in RCBD with three replications. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…in Ethiopia in a Cambisol and Chernozem soil type evaluated the Soil management practices (minimum tillage (MT) and CT) and they also observed an improvement in SOC and TN through MT compared to CT. Numerous other studies in SSA also have recommended conservation practices for enhancing SOC and other properties involved in soil aggregation (ASFAWESEN MOLLA et al, 2021;GITHINJI et al, 2011;GOTOSa et al, 2011;NAAB et al, 2017;NWACHUKWU et al, 2020).…”
Section: Structure and Aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…in Ethiopia in a Cambisol and Chernozem soil type evaluated the Soil management practices (minimum tillage (MT) and CT) and they also observed an improvement in SOC and TN through MT compared to CT. Numerous other studies in SSA also have recommended conservation practices for enhancing SOC and other properties involved in soil aggregation (ASFAWESEN MOLLA et al, 2021;GITHINJI et al, 2011;GOTOSa et al, 2011;NAAB et al, 2017;NWACHUKWU et al, 2020).…”
Section: Structure and Aggregationmentioning
confidence: 99%
“…In turn, residue retention in CA slows the rate of water flow during rainfall, thus allowing the soil to absorb and store more water. Studies by ASFAWESEN MOLLA et al (2021) reported an increase in total porosity under zero tillage and in zero tillage (ZT) coupled with intercropped treatments. Correspondingly, other researchers observed an increase in BD in NT treatment relative to CT (NAAB et al, 2017;SERME et al, 2015).…”
Section: Bulk Density and Total Porositymentioning
confidence: 99%
See 1 more Smart Citation